Health care seeking behaviour of women during pregnancy in rural south India: a qualitative study - Vincent, Antony; Keerthana, K.; K., Damotharan; Newtonraj, Ariarathinam; Bazroy, Joy; Manikandan, Mani (International Journal Of Community Medicine And Public Health, 2017)
Background: Antenatal care is an important indicator in any health system. Through our study we intended to assess the perception of pregnant women regarding health seeking behaviour and awareness about complications during pregnancy. Methods: A qualitative study was carried out in August 2016, among the 41 pregnant women over 27 weeks of gestation in a rural area of south India. Women were selected randomly from the routine surveillance system maintained by Pondicherry Institute of Medical Sciences – Rural Health Training Centre, Chunampet, Kancheepuram District. Interviews audio recorded. After verbatim, manual coding and analysis was done based on pre decided eight themes. Results: In general all the antenatal women aware of the importance of regular antenatal check up. Knowledge regarding complications and danger sign was not adequate. Most of the women in rural area seek care in government facility due to its availability, accessibility and affordability. Decision making in health care is mostly taken by their husbands. Transportation has been identified as a barrier in seeking health care. Conclusions: Although few of the antenatal mothers in the study population were aware about some complications of pregnancy, but in general knowledge among most of the women was inadequate. There is a need for creating awareness among the antenatal mothers about common complications in pregnancy. On the other hand, the notion of routine care seeking during the antenatal period seems to be well rooted among the study population which is a very good sign. It is a good opportunity and is foundational to all other interventions relating to betterment of antenatal care in the community.